2020
DOI: 10.1155/2020/6462034
|View full text |Cite
|
Sign up to set email alerts
|

A Pseudodynamic Approach of Seismic Active Pressure on Retaining Walls Based on a Curved Rupture Surface

Abstract: Reasonable determination of the magnitude and distribution of dynamic earth pressure is one of the major challenges in the seismic design of retaining walls. Based on the principles of pseudodynamic method, the present study assumed that the critical rupture surface of backfill soil was a composite curved surface which was in combination with a logarithmic spiral and straight line. The equations for the calculation of seismic total active thrusts on retaining walls were derived using limit equilibrium theory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Yan et al [22] determined the distribution of earth pressure by differentiating the influences of the total active force's starting phase, amplification factor, and soil friction angle on the distribution. Levesque et al [14] demonstrated that the accuracy of the Marston approach for estimating horizontal earth pressure would be improved by using K-values that are acquired as a function of back fill geotechnical parameters and also excavation geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al [22] determined the distribution of earth pressure by differentiating the influences of the total active force's starting phase, amplification factor, and soil friction angle on the distribution. Levesque et al [14] demonstrated that the accuracy of the Marston approach for estimating horizontal earth pressure would be improved by using K-values that are acquired as a function of back fill geotechnical parameters and also excavation geometry.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical simulation makes clear about the significance of adopting a distinct earth pressure coefficient value (𝐾) for the flux's direction of convergence and divergence. Yan et al (2020) determined the distribution of earth pressure by contrasting the impacts of the total active force on the beginning phase, the amplification factor, and the angle of soil friction. The limit equilibrium analysis method is also demonstrated in this study for determining the non-linear distribution of the active earth pressure on stiff retaining walls with constrained backfills (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1). This study presented the idea that soil deflection plays a more significant role with the narrower width of the backfill and the inclination angle of the triangular failure wedge is connected to the value of the internal friction angle of the solids (Yan et al, 2020). Based on laboratory studies or analytical and numerical models, different researchers proposed various values for the earth pressure coefficient (𝐾).…”
Section: Introductionmentioning
confidence: 99%